Identification of cortactin molecular forms in human urine and their possible diagnostic value - M. Starykovych; S. Souchelnytskyi; O. Fayura; O. Abrahamovych; M. Abrahamovych; N. Lukavetskyy; R. Stoika; Y. Kit (The Ukrainian Biochemical Journal, 2021)
The protein composition of human urine reflects changes in the biochemical and physiological status of an individual and has an essential diagnostic value. Using precipitation/extraction methods we isolated a protein with Mr ~100 kDa in a human urine. MALDI TOF/TOF mass spectrometry identified this protein as human Src protein kinase substrate cortactin (UniProtKB/Swiss-Prot: Q14247). Screening of urine samples using Western blotting with specific anti-human cortactin antibodies revealed different proteins immunologically related to cortactin in healthy humans and patients with liver cirrhosis and lung cancer diseases. These data suggest that the level of cortacins isoform in urine might serve as a potential marker for testing acute and systemic diseases.